2020
DOI: 10.3390/cells9112508
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Manifestations of COVID-19 Infection

Abstract: SARS-CoV-2 induced the novel coronavirus disease (COVID-19) outbreak, the most significant medical challenge in the last century. COVID-19 is associated with notable increases in morbidity and death worldwide. Preexisting conditions, like cardiovascular disease (CVD), diabetes, hypertension, and obesity, are correlated with higher severity and a significant increase in the fatality rate of COVID-19. COVID-19 induces multiple cardiovascular complexities, such as cardiac arrest, myocarditis, acute myocardial inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
154
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 148 publications
(217 reference statements)
7
154
0
8
Order By: Relevance
“…It is reported that hospitalized patients develop acute COVID‐19 cardiovascular syndrome (ACovCS), which is mostly presented as an acute cardiac injury. Myocardial injury is common among patients with COVID‐19 infection and highly correlates with disease severity and in‐hospital mortality 24–27 . Till now, there are several speculations on the specific mechanism of myocardial injury induced by SARS‐CoV‐2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that hospitalized patients develop acute COVID‐19 cardiovascular syndrome (ACovCS), which is mostly presented as an acute cardiac injury. Myocardial injury is common among patients with COVID‐19 infection and highly correlates with disease severity and in‐hospital mortality 24–27 . Till now, there are several speculations on the specific mechanism of myocardial injury induced by SARS‐CoV‐2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, as currently there is no evidence proven and disease-specific medical treatment (despite potential beneficial effects of corticosteroids) available, current intensive care treatment for CARDS is mostly symptomatic/supportive and in line with ARDS recommendations. In addition, despite severe hypoxemic respiratory failure, severe COVID-19 may be associated with additional organ dysfunctions, including cardiac/cardiovascular [ 20 , 21 ], neurological/cerebrovascular [ 22 , 23 ], and/or renal dysfunction [ [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%
“…Precise mechanisms by which hypertension and diabetes are “Covid-19 enhancers” are under investigation [20] . The role of inflammation, oxidative stress, endothelial damage, microvascular damage and cytokine storm alterations may be the link [ 21 , 22 ]. Nevertheless, these explanations are beyond the purpose of our study.…”
Section: Discussionmentioning
confidence: 99%